DDT & deltamethrin resistance status of known Japanese encephalitis vectors in Assam, India - Dhiman, Sunil (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND & OBJECTIVE: Japanese encephalitis (JE) outbreaks are common in Assam, northeastern State of India. Information on resistance in known JE vectors in the affected area is important for effective control measures. This study was undertaken to determine the species abundance of JE vectors endemic to Sibsagar district of Assam, and their susceptibility against DDT and deltamethrin. METHODS: Adult mosquitoes were collected using CDC light trap and aspirators from human dwellings from 13 endemic villages falling under three Primary Health Centres. Collected mosquitoes were identified and unfed female mosquitoes were used for DDT and deltamethrin sensitivity bioassay. The bioassay was performed following WHO protocol using standard susceptibility test kit. Knockdown time (KDT) was monitored at every 10 minutes intervals, whereas mortalities were recorded 24 h post-exposure. Vector density and resistance status were mapped using geographic information system (GIS) technique. RESULTS: A total of 7655 mosquitoes were sampled under three genera, i.e. Anopheles, Culex and Mansonia, and nine species, the JE vector Cx. vishnui group (31.78%) was the most predominant species, followed by Ma. uniformis (16.81%) and Ma. indiana (16.45%). All vector species were suspected to be resistant to DDT and sensitive to deltamethrin, except Ma. indiana, which was suspected to deltamethrin resistant. The KDT(50) and KDT(95) values of vector mosquitoes for DDT were significantly higher as compared to deltamethrin. The probit model used to estimate KDT(50) and KDT(95) values did not display normal distribution of percentage knockdown with time for all the vectors tested for DDT and deltamethrin, except for Ma. indiana for deltamethrin assay and Cx. gelidus for the DDT assay. INTERPRETATION & CONCLUSION: Differences in insecticide resistance status were observed between insecticides and vector species. The results of this study provided baseline data on insecticide resistance in known JE vectors of Sibsagar, Assam. The maps generated may allow better communication in control operations and comparison of changes in susceptibility status of these vectors over time.